2014
DOI: 10.5018/economics-ejournal.ja.2014-11
|View full text |Cite
|
Sign up to set email alerts
|

External Factors Affecting Investment Decisions of Companies

Abstract: In this paper, we attempt to investigate the importance of certain external factors on the investment decisions made by Polish companies. With the use of data from the tailor-made Survey on Receivables, we (1) examine factors influencing investment decisions of companies in Poland; (2) assess the relation between branch, company size and investment factors; (3) evaluate the importance of the investment factors; and (4) determine the relative influence of these factors on the company-level investment reductions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 34 publications
0
11
0
2
Order By: Relevance
“…The corporate investment that included as dependent variables has been measured as investment in fixed asset (property, plant and equipment) or capital expenditures divided by total assets. This proxy has widely used in prior studies to measure the firm investment (Bialowolski & Bialowolska, 2013; Gulen, 2016; Hamzah, 2017; Onwe & Olarenwaju, 2014; Wuhan & Khurshid, 2015). Similarly, the macroeconomic variables are inflation rate, interest rate, GDP growth rate, foreign direct investment and financial sector development.…”
Section: Methodsmentioning
confidence: 99%
“…The corporate investment that included as dependent variables has been measured as investment in fixed asset (property, plant and equipment) or capital expenditures divided by total assets. This proxy has widely used in prior studies to measure the firm investment (Bialowolski & Bialowolska, 2013; Gulen, 2016; Hamzah, 2017; Onwe & Olarenwaju, 2014; Wuhan & Khurshid, 2015). Similarly, the macroeconomic variables are inflation rate, interest rate, GDP growth rate, foreign direct investment and financial sector development.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Bialowolski and Weziak-Bialowolski (2013) examined the external factors that influence corporate investments in Poland. Using variables including the company's receivables, firm size and survey data obtained from individual firms, with a root mean-square error of measurement estimation technique, the study found that payment delay is a vital factor affecting corporate investments.…”
Section: Market and Macroeconomic Uncertaintiesmentioning
confidence: 99%
“…The variables in the model described in Equation 2, scaled by the firm's capital stock, were used to account for differences in firm sizes, which, according to Bialowolski and Weziak-Bialowolski (2013), influence corporate investments. Uncertainty constitutes the variable of interest, and the inclusion of market and macroeconomic uncertainties in the model is driven by the theoretical and empirical background, indicating that they affect corporate investment decisions.…”
Section: Variables Description and Model Specificationmentioning
confidence: 99%
“…Ağca and Mozumdar (2017) find that internal funds and cash flows are important and significant determinants of firm investment. Bialowolski and Weziak-Bialowolska (2014) conduct a study on Polish companies and found that payment delays and legal and macroeconomic factors considerably affect firm investment decisions. Their study also shows that cash flow sensitivity has a significant negative impact on firm investment at the time of high growth rate options.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%